Influence of two different methods of nutrition education on the quality of life in children and adolescents with type 1 diabetes mellitus - a randomized study - Karolina Dłużniak-Gołaska; Mariusz Panczyk; Agnieszka Szypowska; Beata Sińska; Dorota Szostak-Węgierek (National Institute of Public Health - National Institute of Hygiene, 2020)
Background. Nutrition education is one of the most important factors determining the effectiveness of treatment and maintaining an adequate quality of life (QoL) in children and adolescents with type 1 diabetes. Objective. The primary objective was to compare the influence of two methods of nutrition education on the QoL. The secondary objective was to identify other determinants of the QoL. Material and Methods. A randomized single-blind study was conducted between October 2017 and April 2019 at the Children's Clinical Hospital in Warsaw. The study included 170 patients (aged 8-17) with at least 1-year history of type 1 diabetes, treated with insulin pumps. The participants were randomly divided into two groups: a control group (C) - traditional/ informative education methods, and an experimental group (E) - modern/interactive methods. PedsQL Diabetes Module 3.0 questionnaire was used in the assessment of the QoL. Total PedsQL score was the primary outcome. The secondary outcomes included the results obtained in five subscales of the questionnaire. The relationships between selected variables and changes in scores were also verified. Results. Data obtained from 136 patients were analyzed. In both groups no significant changes regarding total PedsQL were noted 6 months after the intervention. However, a significant reduction occurred as regards the scores of 'Communication' subscale in group C. Analyzing other determinants of the QoL, significant dependencies were observed between: the level of physical activity and a change in 'Diabetes symptoms' subscale, and the level of parents' education and a change in 'Treatment barriers' subscale. Conclusions. Both methods of nutrition education exerted a comparable influence on the total QoL. However, modern methods were more effective in terms of the improvement in the aspect of communication. Additionally, moderate physical activity and parents' tertiary education constituted valid determinants of various aspects of the QoL in children and adolescents with type 1 diabetes.